Biological control of parthenium (Parthenium hysterophorus): the Australian experience. Issue 10 (3rd October 2018) - Dhileepan, Kunjithapatham; Callander, Jason; Shi, Boyang; Osunkoya, Olusegun O.
ABSTRACT: Parthenium is a Weed of National Significance in Australia. Biological control of parthenium in Australia commenced in 1977 and since then nine insect species and two rust fungi have been introduced and established. Seven of them are widespread, however the time taken for field establishment varied widely between various agents, ranging from one to 15 years. Among them, the stem-galling Epiblema moth, the stem-boring Listronotus weevil, the seed-feeding Smicronyx weevil and the root-feeding Carmenta moth occur in all parthenium-infested areas at high population densities. The leaf-feeding Zygogramma beetle occurs only in central and southern Queensland, and not in northern Queensland. The parthenium summer rust occurs seasonally in central and northern Queensland, while the parthenium winter rust is more widespread in southern Queensland than in central Queensland, but does not occur in north Queensland. The sap-feeding Stobaera planthopper and the leaf-mining Bucculatrix moth established and are widespread, but their damage levels remain very low. The stem-galling Conotrachelus weevil and the stem-boring Platphalonidia moth are believed to be established, but at very low abundance. Biological control has resulted in significant reductions in the abundance and impact of parthenium in Australia. As a result, the area infested with parthenium in central Queensland has declined since the mid-1990s. Due to the absence of many of the effective agents in southern and south-eastern Queensland, agents from central Queensland are being redistributed there. Additionally, based on Australian success, many of these agents have also been introduced into other countries around the world.